Identities and inclusiveness: rethinking social cohesion - Wong, Yasmine (2022)
Identity politics has made salient the link between identities and social cohesion. Real solutions can emerge when a multi-pronged approach is taken to provide diverse communities with equal access, due recognition, and the opportunity to participate in creating a shared vision of inclusiveness and justice.